Trehalose inhibits cell proliferation and amplifies long‐term temozolomide‐ and radiation‐induced cytotoxicity in melanoma cells: A role for autophagy and premature senescence. Issue 7 (29th November 2018) - Allavena, Giulia; Del Bello, Barbara; Tini, Paolo; Volpi, Nila; Valacchi, Giuseppe; Miracco, Clelia; Pirtoli, Luigi; Maellaro, Emilia
Abstract: Cutaneous melanomas frequently metastasize to the brain, with temozolomide (TMZ) plus radiotherapy (RT) offering little control of these lesions. We tested whether trehalose, a natural glucose disaccharide proved to induce autophagy, could enhance the effect of TMZ and ionizing radiation (IR). In two melanoma cell lines (A375 and SK‐Mel‐28), which greatly differ in chemosensitivity and radiosensitivity, trehalose significantly inhibited short‐term cell proliferation and also enhanced IR‐induced cytostasis. Interestingly, in TMZ‐resistant SK‐Mel‐28 cells, trehalose was more effective than TMZ, and combined trehalose + TMZ further reduced cell proliferation. In long‐term experiments, colony‐forming capacity was dramatically reduced by trehalose, and even more by combined trehalose + TMZ or trehalose + IR. In resistant SK‐Mel‐28 cells, although growth was inhibited most with trehalose + TMZ + IR‐6 Gy combined treatment, it is notable that trehalose + TMZ treatment was also very effective. Along with a direct antiproliferative effect, two further mechanisms may explain how trehalose potentiates TMZ‐ and IR‐induced effects: the remarkable trehalose‐stimulated autophagy in A375 cells, which were sensitive to TMZ‐ and IR‐induced apoptosis; and the notable trehalose‐stimulated premature senescence in SK‐Mel‐28 cells, which were resistant to apoptosis and less prone to autophagy. In normal melanocytes, trehalose induced a minor autophagy and cell proliferation inhibition, without affecting cell viability; moreover, when trehalose was used in combination with TMZ, the slight TMZ‐induced cytotoxicity was not significantly reinforced. Together, our results suggest that trehalose, a safe nutrient supplement able to cross the blood–brain barrier, is a promising candidate, worthy to be further explored in vivo, to augment the therapeutic efficacy of TMZ and RT in melanoma brain metastases. Abstract : Trehalose, a natural disaccharide, inhibits short‐term cell proliferation and, even more, colony‐forming capacity in melanoma cells. Moreover, trehalose magnifies temozolomide (TMZ)‐ and irradiation (IR)‐induced cytotoxicity in the long term. Two different cell responses are induced by trehalose: a remarkable autophagy in melanoma cells (A375) sensitive to TMZ‐ and IR‐induced apoptosis, and premature senescence in melanoma cells (SK‐Mel‐28) resistant to apoptosis and less prone to autophagy.